2020
DOI: 10.1162/netn_a_00166
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting correlation-based functional connectivity and its relationship with structural connectivity

Abstract: Patterns of brain structural connectivity (SC) and functional connectivity (FC) are known to be related. In SC-FC comparisons, FC has classically been evaluated from correlations between functional time series, and more recently from partial correlations or their unnormalized version encoded in the precision matrix. The latter FC metrics yields more meaningful comparisons to SC because they capture ‘direct’ statistical dependencies, i.e., discarding the effects of mediators, but their use has been limited beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 83 publications
2
78
0
Order By: Relevance
“…This work opens also the avenue of relating functional brainprints with underlying structural architecture. Recent studies have shown that building FC matrices from (very) long RS fMRI sessions leads to very good proxies for SC 30 . Similarly, it has been shown that longer fMRI sessions (up to a plateau 10 ) improve identification.…”
Section: Discussionmentioning
confidence: 99%
“…This work opens also the avenue of relating functional brainprints with underlying structural architecture. Recent studies have shown that building FC matrices from (very) long RS fMRI sessions leads to very good proxies for SC 30 . Similarly, it has been shown that longer fMRI sessions (up to a plateau 10 ) improve identification.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we calculated FC using a regularized precision approach, which aims to capture only the “direct” connections between brain regions. We chose to use precision-based FC as it was recently shown to result in FC matrices that had stronger correlations with SC than more conventional Pearson correlation-based FC 32 . For completeness and comparison to previous work 24, 25 , Pearson correlation-based FC results are provided in the Supplemental Information.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical, communication, biophysical and machine learning models have been applied to better align FC and SC 3, 7, 8, 38 . Recent work has also found the strength of global SC-FC correlation depends on how FC is calculated 32 . In particular, this work showed FC calculated using partial correlation (precision), which aims to isolate direct and remove the effect of indirect functional connections, had stronger correlations with SC than standard FC calculated using full (Pearson) correlation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations